(untitled) (International Journal of Engineering and Computer Science, 2023)
Existence and unicity of solutions of third order non-linear differential equations is an interesting area of current research and a great deal of work has been done by many authors during the last few years. The idea of matching solutions of two-point boundary value problems at the common point of solutions is very fascinating.